PENGARUH GAYA KEPEMIMPINAN DALAM MENCIPTAKAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT.Lentera Nusatama,Surakarta) - Pradipta, Daksa Adi; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2015)
In attempts of encouraging creation of quality human resource, leadership style is one of factors in which academicians and practitioners of human resource pay attention. The research examines effects of leadership style on working discipline, working motivation, and performance of employees.Subject of the research is employees of PT. Lentera Nusatama of Surakarta. Sample of the research is all members of population, namely 72 respondents. Questionnaire is used to collect data and path analysis with multiple linear regression model approach is used to prove hypotheses of the research.Results of the research obtained a total value of determination coefficient from regression model of 75.3%. It means that leadership style had significant effect on working motivation, working discipline and performance of employees,Â whereas the rest, 24.7%, were affected by other variables. Because values of leadership style, motivation and working discipline was less than 0.05, it can be concluded that a positive effect of leadership style on the working motivation, discipline and performance of employees was found.